Examining the factors structures of brand loyalty of men’s deodorants among generation X and generation Y consumers in Cape Town - Lokosang, Lobojo (School of Management Studies, 2020)
This study examines the structures and reliability of brand loyalty in men’s deodorant consumption, as suggested by Moolla’s (2010) framework. This is due to the fickle or disloyal nature of male Generation X and Generation Y deodorant consumers. Although, the subject of brand loyalty is popular, there is a lack of research in the investigation of Generation X and Generation Y consumers specifically in the men’s deodorant industry in Cape Town. This study attempted to close the gap by examining brand loyalty of Generation X and Generation Y consumers in Cape Town through the brand loyalty framework. Based on Chronbach Alphas, the study assessed the degree to which each factor of deodorant brand loyalty loads unto a construct or internal consistency. This study’s motivation is to attempt to assist management develop appropriate strategies, and to expand the body of knowledge for academics, due to limited information and to pave the way for researchers to explore various product categories specifically utilised by men as well as assist them with a tested brand loyalty framework. A positivist research paradigm provided the belief system in which data for the current study was gathered, analysed and used to provide solutions. A descriptive research design chosen for the study resulted in the application of a quantitative research methodology. With reference to Moolla’s research questionnaire, data for the current study was collected from men between the ages of 36 and 52 (Generation X) and Generation Y (men between the ages of 18 and 35). A total of 245 responses were received from Generation X and Generation Y men who are brand loyal to men’s deodorants and the data were collected by statistically analysing this sample. This research established that there were leading brands that consumers were brand loyal to and that there were dominant brand loyalty influences for both Generation X and Generation Y consumers in the men’s deodorant industry. In addition, it was revealed in the study that the suggested recommendations were that there needs to be further research in the men’s deodorant industry, a comparative study should be conducted, brand loyalty of other product categories should be investigated and marketers should focus on culture as a significant influence of brand loyalty. For future research, it was recommended that this study be continued on a larger scale in the men’s deodorant industry to endorse or rectify the results of this study